1999
DOI: 10.1046/j.1365-2443.1999.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinase‐independent activity of Cdc2/Cyclin A prevents the S phase in the Drosophila cell cycle

Abstract: Background: The Cdc2-dependent inhibition of S phase is required in G2 for the correct ordering of the S and M phases in yeasts and Drosophila. This function of Cdc2 has been ascribed to its ability to phosphorylate replication factors to prevent the assembly of a preinitiation complex at the origin of replication. Whether this is the sole mechanism of S phase inhibition by Cdc2 in higher metazoans is not known because the pleiotropic functions of this essential cell cycle regulator make genetic analysis diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…In fact, there are several protein kinases whose biological activities do not correspond to their in vitro kinase activities (Schwartzberg et al, 1997;Hayashi and Yamaguchi, 1999;Rathjen et al, 1999;Charette et al, 2001;Hu et al, 2001;Hü ser et al, 2001;Hojjati et al, 2007;Chen et al, 2008). Hojjati et al (2007) reported that the autophosphorylation and substrate phosphorylation activities of animal aCaMKII are not required for it to function in the modulation of short-term presynaptic plasticity, suggesting that aCaMKII plays a structural role rather than an enzymatic role (Hojjati et al, 2007).…”
Section: Biological Activity Of Ccamk Is Not Solely Defined By In Vitmentioning
confidence: 99%
“…In fact, there are several protein kinases whose biological activities do not correspond to their in vitro kinase activities (Schwartzberg et al, 1997;Hayashi and Yamaguchi, 1999;Rathjen et al, 1999;Charette et al, 2001;Hu et al, 2001;Hü ser et al, 2001;Hojjati et al, 2007;Chen et al, 2008). Hojjati et al (2007) reported that the autophosphorylation and substrate phosphorylation activities of animal aCaMKII are not required for it to function in the modulation of short-term presynaptic plasticity, suggesting that aCaMKII plays a structural role rather than an enzymatic role (Hojjati et al, 2007).…”
Section: Biological Activity Of Ccamk Is Not Solely Defined By In Vitmentioning
confidence: 99%
“…Moreover, E2F transcription factors have been found to interact with A2-type cyclins (J. Boruc, L. De Veylder, 30.1 6 1.4 31.4 6 0.7 31.6 6 0.7 31.9 6 1.1 8C 22.7 6 1.6 21.4 6 1.0 29.6 6 1.7 28.1 6 2.1 16C 11.8 6 0.8 13.2 6 1.2 7.9 6 0.4 9.4 6 1.1 +10 mM b-estradiol 2C 27.2 6 2.5 35.7 6 5.1 24.5 6 1.1 40.2 6 5.0 4C 26.9 6 1.7 25.0 6 2.6 29.4 6 1.9 24.0 6 1.4 8C 27.7 6 1.6 31.9 6 1.6 36.5 6 1.4 31.9 6 3.0 16C 16.2 6 0.5 7.2 6 2.6 9.5 6 1.9 3.9 6 0.7 and E. Russinova, unpublished data), another indication that A2-type cyclins might play a role during the S phase itself. In mammals, E2F activity is regulated by CDK2-cyclin A phosphorylation (Krek et al, 1994;Xu et al, 1994;Kitagawa et al, 1995;Hayashi and Yamaguchi, 1999;Morris et al, 2000). Inactivation of E2Fs by CDK2 phosphorylation promotes the mitotic cell cycle by driving cells into the G2 phase.…”
Section: Cdkb1;1 and Cyca2;3 Colocalize In The Nucleusmentioning
confidence: 99%
“…The physical interaction between the recombinant CDT1a and CYCA2;2 proteins in an in vitro pull-down experiment (del Mar Castellano et al, 2004) supports this possibility. Animal cyclin A/CDKs also negatively regulate G1/S-related transcription factors, including E2F-DP (Dynlacht et al, 1994;Krek et al, 1994;Xu et al, 1994;Hayashi and Yamaguchi, 1999). In a transcription analysis using real-time quantitative PCR, however, significant differences in the transcript level of CDC6a, which is regulated by E2Fa-DPa , could not be detected among the wild type, the mutant, and the CYCA2;3-GFP and mDB-CYCA2;3-GFP overexpressors (see Supplemental Figure 5 online), suggesting that CYCA2;3 is not involved in transcriptional regulation.…”
Section: Molecular Mechanism For the Negative Regulation Of Endocyclesmentioning
confidence: 99%